Ocular Safety of Intravitreal Injections of Age-Related Macular Degeneration Treatments in a Prospective Observational Cohort Study in Europe - Kui Huang; Marla B. Sultan; Duo Zhou; Charles S. Tressler; Jingping Mo (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2015)
Purpose: Estimate the incidence of pertinent ocular adverse events (POAEs) related to intravitreal (IVT)injections for age-related macular degeneration (AMD) treatments in Europe. Methods: Ophthalmologists prospectively followed patients, who received IVT injection treatment for AMD including Macugen®, Lucentis®, and Avastin® at ophthalmic clinical centers in Europe, and determined outcomes of interest as clinically appropriate up to two years. Main outcomes included endophthalmitis, retinal detachment, vitreous hemorrhage, retinal tear, traumatic cataract, and increased intraocular pressure (IOP). Results: 501 patients from 69 sites in 13 countries were enrolled.The mean age was 73.6 years. Most patients received monotherapy (80.4%), were white (97.4%), and never smoked (65.3%). The total number of IVT injections for AMD treatment was 3,754 among those patients. The incidence of POAEs was low overall (0 to 1.28% per injection, 0 to 6.6% per patient).Increased IOP was the most frequently reported POAE. There was a positive association between the incidence of increased IOP and the number of injections received.Endophthalmitis was not reported. Conclusions: The incidence of POAEs related to IVT injections in this study was low and similar to that reported in the literature.